2021
DOI: 10.1186/s40359-021-00697-1
|View full text |Cite
|
Sign up to set email alerts
|

Grandiose and vulnerable narcissism, identity integration and self-control related to criminal behavior

Abstract: Background Although systematic research on narcissism has been conducted for over 100 years, researchers have only recently started to distinguish between grandiose and vulnerable narcissism in relation to criminal behavior. In addition, there is some evidence suggesting that identity integration and self-control may underlie this association. Therefore, the present study aimed to develop a theory-driven hypothetical model that investigates the complex associations between grandiose and vulnera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 74 publications
3
12
0
Order By: Relevance
“…Whereas grandiose narcissism manifests itself in exaggerated self-esteem, grandiosity, and an unrealistic sense of superiority, vulnerable narcissism manifests itself in low self-esteem, hypervigilance, and social withdrawal (Miller et al, 2011(Miller et al, , 2012Pincus, 2011). Research confirms that particularly vulnerable narcissism relates to the reported experience of identity impairment, whereas grandiose narcissism predicts the reported experience of adaptive self-functioning (Bogaerts et al, 2021c;Huxley et al, 2021). As the ADP-IV mostly captures grandiose narcissism, we may have obtained mixed results.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Whereas grandiose narcissism manifests itself in exaggerated self-esteem, grandiosity, and an unrealistic sense of superiority, vulnerable narcissism manifests itself in low self-esteem, hypervigilance, and social withdrawal (Miller et al, 2011(Miller et al, , 2012Pincus, 2011). Research confirms that particularly vulnerable narcissism relates to the reported experience of identity impairment, whereas grandiose narcissism predicts the reported experience of adaptive self-functioning (Bogaerts et al, 2021c;Huxley et al, 2021). As the ADP-IV mostly captures grandiose narcissism, we may have obtained mixed results.…”
Section: Discussionmentioning
confidence: 87%
“…Remarkably, whereas PDs were generally unrelated to adaptive identity functioning, a positive association between narcissistic PD and consolidated identity was found. Previous research has generated mixed results with some studies showing positive associations between narcissistic PD and identity integration (Bogaerts et al, 2021c; Huxley et al, 2021), and others yielding opposite results (Anderson & Sellbom, 2018; Liggett et al, 2017; Sleep et al, 2019). The inconsistency may be explained by the distinction between grandiose and vulnerable narcissism.…”
Section: Discussionmentioning
confidence: 99%
“…However, not all individuals with narcissism solely display a grandiose sense of self [53]. In fact, although systematic research on narcissism has been conducted for over 100 years, researchers only recently tried to distinguish between two different narcissism varieties: i.e., the grandiose (namely 'overt') and the vulnerable (namely 'covert') narcissism [53,54]. In both forms the individual strongly believes that he/she has a special "uniqueness and superiority", displays high levels of self-love, a strong sense of entitlement, and poses a greater emphasis on self-serving bias [55].…”
Section: Narcissismmentioning
confidence: 99%
“…However, there are also considerable differences between grandiose and vulnerable narcissism that emphasize the dual nature of this personality trait [56]. The grandiose narcissism discloses a high self-esteem level and a low tolerance to criticism, an unrealistic sense of superiority, as well as admiration seeking, arrogance and a tendency to depreciate others' behaviors [53][54]. Contrarily, the individual with a vulnerable narcissism presents a low self-esteem, hypervigilance, social withdrawal and emotional hypersensitivity, as well as introversion and self-devaluation [54,57].…”
Section: Narcissismmentioning
confidence: 99%
See 1 more Smart Citation